The ethical values of administrative leaders and their relationship to the innovative behavior of subordinates An exploratory study of a sample of subordinates in the Social Security Fund, Sabha office (Economic studies journal, 2020)
This study sought to reveal the relationship and impact between the ethical values of administrative leaders and the innovative behavior of subordinates in the Social Security Fund Sabha office, where the problem of the study was the following question: Do moral values of leaders have a role in developing the innovative behavior of subordinates? Then, selecting a soft sample consisting of (38) employees in the fund, to achieve the goals of the study and then adopting the descriptive analytical approach, and the study started from the hypothesis that there is a statistically significant relationship at the level of significance (0.05≤ a) between the ethical values of administrative leaders and developing the innovative behavior of subordinates Then, building a questionnaire that consisted of (37) paragraphs divided into two parts, the first relates to the dimensions of the moral values of administrative leaderships, and the second to the innovative behavior of subordinates. After conducting statistical methods for the validity and consistency of the questionnaire that were applied to the individuals of the sample, the results indicated that all dimensions of the ethical values of administrative leaders are positively and strongly linked to the innovative behavior of subordinates.
Keywords: moral values, administrative leadership, innovation, innovative behavior, social security